Understanding seasonal water clarity dynamics of Lake Dahuchi from In Situ and remote sensing data - Wu, G.; Leeuw, Jan de; Liu, Y. (Springer, 2009)
Obtaining, analyzing and understanding the seasonal dynamics of water clarity is of importance for understanding and managing lakes and sustaining their ecosystem services. This study aimed to explore the seasonal dynamics of water clarity and to analyze how water level, wind velocity and total precipitation influence this dynamics in Lake Dahuchi, China. The Secchi disk depths recorded in the field and derived from Moderate Resolution Imaging Spectroradiometer (MODIS) images together demonstrated a seasonal pattern of water clarity, which was lower in winter and spring, increased in April or May to reach the highest values in summer, upon which it gradually declined from September onward. Piecewise linear regression analysis between water clarity and water level showed that water level could explain 70% of the variation of the logarithm of Secchi disk depth. The water clarity of Lake Dahuchi was primarily controlled by suspended sediment, while the seasonal variation of water level induced different sediment resuspension, thus we concluded that the water clarity seasonal dynamics of Lake Dahuchi was mainly regulated by seasonal variation of water level.